Application of Low Stray Inductance Bus-bar Technology in IGBT Converter - CHEN Mingyi; MA Bole; CHEN Yuqi; WANG Xiong (Kongzhi Yu Xinxi Jishu)
It studied laminated busbars which were widely used in IGBT converters, analyzed the generation of overvoltage on switching devices and the way to limit them. The basic model of laminated busbar was established. It presented composition and calculated methods of the total stray inductance in commutation circuits. Moreover, the calculated results were compared with simulation and experimental results. Several design rules of laminated busbar were proposed to optimize EMC performance.